2022
DOI: 10.3390/w14132130
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ammonium–N and Nitrate–N Contamination of Shallow Groundwater in a Complex Agricultural Region, Central Western Taiwan

Abstract: The characteristics of nitrogen contamination of shallow groundwater were evaluated through current status analysis and trend detection of ammonium–N and nitrate–N concentrations under various cropping patterns to assess the effectiveness of rational fertilization in the Choushui River alluvial fan, central Western Taiwan. The influence of cropping patterns on both ammonium–N and nitrate–N contamination associated with redox conditions/dissolved oxygen (DO) in shallow groundwater was also discussed in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The reasonable utilization of groundwater resources as agricultural irrigation can increase crop productivity and reduce the costs of the irrigation canal system. In the paper "Assessment of Ammonium-N, and Nitrate-N Contamination of Shallow Groundwater in a Complex Agricultural Region, Central Western Taiwan" [3], nitrogen contamination in shallow groundwater in a complex agricultural region in Taiwan was evaluated. The study analyzed the current status of Ammonium-N and Nitrate-N concentrations under various cropping patterns to assess the effectiveness of reasonable fertilization.…”
Section: Overview Of the Contributions Of The Special Issuementioning
confidence: 99%
“…The reasonable utilization of groundwater resources as agricultural irrigation can increase crop productivity and reduce the costs of the irrigation canal system. In the paper "Assessment of Ammonium-N, and Nitrate-N Contamination of Shallow Groundwater in a Complex Agricultural Region, Central Western Taiwan" [3], nitrogen contamination in shallow groundwater in a complex agricultural region in Taiwan was evaluated. The study analyzed the current status of Ammonium-N and Nitrate-N concentrations under various cropping patterns to assess the effectiveness of reasonable fertilization.…”
Section: Overview Of the Contributions Of The Special Issuementioning
confidence: 99%
“…This was confirmed in a study by Daniels et al [64], who demonstrated that ammonium leaching was greater in the acidic upland peatlands of Great Britain. Part of the N-mineral is released in the form of ammonium, which is not readily available to plants and remains in the soil, and part is released in the nitrate form, which is the more labile form and is leached into the groundwater after phytosorption [65].…”
Section: Mineral Nitrogen Content In Groundwatermentioning
confidence: 99%